Effect of dopants and microstructure on the electrochemical cyclic stability of layered P2-type Na0.67MnO2 prepared by different chemical routes: An experimental and theoretical study. Issue 4 (15th February 2023) - Venkatesh, Manchala; Priyanga, G. Sudha; Sharma, Sonia; Kanta, P. Laxman Mani; Thomas, Tiju; Gopalan, R.; Das, Bijoy
Abstract: High specific capacity layered transition metal oxide, Nax MnO2 is considered a potential cathode for sodium-ion batteries (SIBs). However, its poor capacity retention due to irreversible phase transitions during sodium ion insertion/extraction remains a critical challenge for practical applications. Herein, we report Fe and Co co-doped P2-type Na0.67 MnO2 cathode material prepared via different facile chemical routes to understand the effect of dopants and microstructure on its electrochemical cyclic stability. The Rietveld refinement analysis depicts an increase in lattice parameter c of Fe and Co doped materials as compared to parent material; thereby favouring sodium-ion storage (in turn enhancing and stabilizing specific capacity). XPS analysis confirms the presence of Mn in both 3+ and 4+ oxidation states; whereas Fe and Co in 3+ oxidation states occupy Mn 3+ in Na0.67 MnO2 . Both experiment and ab initio magnetic calculations show a reduction in Mn 3+ content after Fe and Co doping, reducing the tendency for Jahn-Teller distortion. This is concomitant with Fe and Co doping showing improved cyclic stability when cycled under similar conditions. At 0.1 C (where 1 C = 174 mAh g −1 ), Fe and Co-doped Na0.67 MnO2 showed significant improvement with higher discharge specific capacities of 80 and 103 mAh g −1 even after 60th cycle when compared to 36 mAh g −1 after 25th cycle for the parent material Na0.67 MnO2 . Highlights: Novel co-precipitation and microwave-assisted synthesis of Na0.67 (Mn0.5 Fe0.25 Co0.25 )O2 . Improved cyclic stability through sequential doping of Fe and Co into Na0.67 MnO2 . Effect of microstructures on the electrochemical performance of Na0.67 MnO2 . Explanation of improved electrochemical performance through density functional theory. Structure-property correlation through experiment and theoretical study.